Private captain : a story of Gettysburg - Crisp, Marty (New York : scholastic, 2003)
In 1863 Pennsylvania, twelve-year-old Ben and his dog Captain set off in search of Ben's brother, who is missing from the Union Army.
G5
Keywords: Gettysburg, Battle of, Gettysburg, Pa., 1863 -- Juvenile fiction; Gettysburg, Battle of, Gettysburg, Pa., 1863 -- Fiction; Dogs -- Fiction; Brothers -- Fiction; United States -- History -- Civil War, 1861-1865 -- Fiction; Gettysburg (Pa.) -- Fiction